EFFICACY OF KINESIOTHERAPY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND EXCESS BODY WEIGHT - Makarchuk, N. R.; Bakaliuk, T. H.; Chubei, K. I.; Stelmakh, H. O. (Nursing, 2024)
Introduction. Chronic obstructive pulmonary disease (COPD) is a serious medical problem that has a significant impact on the quality of life of millions of people around the world. The aim of the study – to evaluate the effectiveness of kinesiotherapy in patients with chronic obstructive pulmonary disease and overweight. The main part. We examined 27 patients with COPD and overweight. Patients were divided into 2 groups that differed in the treatment regimen: the control group (CG) – 13 patients received only standard treatment, and the main group (MG) – 14 patients in addition to the protocol treatment were engaged in kinesiotherapy (dosed walking and Qigong exercises) for 8 weeks. The effectiveness of rehabilitation was assessed before and after 8 weeks of treatment using the mMRC dyspnea severity scale, COPD Assessment Test (CAT) and spirometry, body mass index (BMI). According to the mMRC dyspnea scale, there were no patients without dyspnea before treatment, but after rehabilitation, the level of dyspnea in OG patients was 2.0 (2.0; 4.0) points, in OG patients – 3.0 (2.0; 4.0), respectively. The mean score of the COPD test before treatment was (14.8±6.13) points and did not differ statistically between groups (p<0.05), after 8 weeks it was 10.33±5.11 points and statistically significantly differed between groups (p<0.05) due to a better result in the OG. Indicators of external respiratory function according to spirometry improved in both groups: FEV1 increased by 2.5 % in the CG and 6.4 % in the OG, FEV1 increased by 3.5 % in the CG and 14.36 % in the OG, FEV1/FEV1 increased by 15.6 % in the OG and 1.96 % compared to the data before treatment, however, a better result was observed in the OG in contrast to the CG and was statistically significant (p<0.05). The body mass index of the studied patients before treatment averaged (28.42±1.4) and was not statistically different between the groups (p>0.05). However, after the application of rehabilitation measures, a more effective result was observed in the OG and amounted to (25.66±0.59). Conclusions. The results of this study indicate the effectiveness of rehabilitation treatment in patients with chronic obstructive pulmonary disease and overweight. Patients who underwent rehabilitation measures demonstrated a significant reduction in body mass index, improvement in physical activity and external respiratory functions.